Stress levels, coping strategies, and mental health literacy among secondary school students in Kenya - Ayiro, Lilian; Misigo, Bernard Lushya; Dingili, Rodgers (Frontiers in Education, 2023)
Introduction Mental health literacy could be a protector from stress and other mental health problems. Statistics in sub-Saharan Africa estimate that up to 20% of children and adolescents experience mental health problems due to stress. Research has also shown that there is a bidirectional association between positive coping and mental health literacy. Nonetheless, little is known about stress levels, coping strategies, and mental health literacy of secondary school students in Kenya. This study sought to answer the following questions: What is the stress level of students in secondary schools in Kenya? What is the association between stress levels and coping strategies of learners? What is the mental health literacy level of learners in secondary schools in Kenya? Methods The study employed a sequential explanatory mixed methods research design by carrying out a quantitative study to ascertain stress levels and coping strategies and a qualitative study to explore the mental health literacy of the students. A total of 400 secondary school students aged 16–22 years participated in the study. Quantitative data were analyzed using descriptive and inferential statistics whereas qualitative data was analyzed thematically. Results Based on these results, the majority of students were moderately 244 (66%) and highly 112 (31%) stressed. Only 11 students (3%) reported low stress levels. The study also indicated a positive significant association between stress and avoidance coping strategy (r = 0.11, p < 0.05). Qualitative data revealed varied conceptualizations of mental health. The following themes emerged: the students conceptualized mental health as help offered to people who are stressed to help them reduce stressors, others felt that it was a state of being at peace with one’s self and being able to think and act soundly, whereas others felt that mental health is severe mental disorder or illness. Students further attributed stress to school, peer, and home pressure. Discussion Lastly, although the students believed that seeking emotional, social, and psychological support was the best way to cope with stress, they feared seeking this support from teachers and peers. There was no evidence of students seeking support from parents. This study contributes to the Group Socialization Theory that suggests that peers become the primary social agents of adolescents outside the confinement of their homes. It provides essential information for developing awareness programs on mental health issues in Kenyan secondary schools. It also highlights a need to equip students with skills so that they can offer peer-to-peer support in times of distress.